Nigeria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues and Statistical Appendix paper presents an assessment of Nigeria's past economic reform efforts-in particular the program supported by the 2000-01 Stand-By Arrangement (SBA). The paper also reviews weaknesses in the current fiscal management framework in Nigeria and proposes reforms to further strengthen the budget process. It describes weaknesses in the current public debt management framework and the government's reform strategy. It highlights the reform implication and addresses further actions that will be needed to put the government's domestic debt reform strategy on a solid foundation.